Penerapan Metode Additive Ratio Assessment (ARAS) Dalam Pemilihan Guru Terbaik - Sitna Hajar Hadad (PT. Tech Cart Press, 2023)
The selection of the best teachers is a crucial process in improving the quality of education because teachers have a central role in shaping and developing the potential of students. This study aims to select the best teachers by applying the ARAS method to provide recommendations to school management in determining the best teachers. The ranking results were obtained by the best teacher by teacher 8 with a final grade of 0.962952 getting rank 1, teacher 1 with a final grade of 0.929876 getting rank 2, and teacher 4 with a final grade of 0.925905 getting rank 3.